Increasing Environmental Awareness in Early Childhood 4-5 Years through the Problem-Based Learning Grophy Garbage Approach - Tazkiya Asti Fatikha; Sri Katoningsih (Universitas Muhammadiyah Surakarta, 2025)
There is an urgent need to instill environmental awareness in early childhood (4-5 years old) at PGRI Jati Kindergarten. The purpose of this study was to test the effectiveness of the Problem-Based Learning (PBL) approach with the